N-(3-Oxododecanoyl)-Homoserine Lactone Induces Intestinal Barrier Damage in Piglets via the Lipid Raft-Mediated Apoptosis Pathway - Yang Yang; Xin Zhang; Jin Yang; Ziyan Wu; Junpeng Li; Ruilong Song; Chuang Meng; Guoqiang Zhu (Veterinary Sciences)
Quorum sensing (QS) is a process by which bacteria sense their population density and regulate behavior accordingly. QS not only regulates bacterial virulence but also directly influences host cells. Previous studies have shown that QS is strongly associated with piglet intestinal health, but the mechanism is not yet clear. For the first time, we have confirmed in a piglet animal model that OdDHL directly damages intestinal cells in weaned piglets, disrupting the intestinal barrier. We also provide a preliminary exploration of the underlying mechanism of these effects. TUNEL assays confirmed that damage to the piglet intestinal barrier coincided temporally and spatially with dysregulated apoptosis. Lipid rafts, key components of the cell membrane, are involved in many biological processes, including the activation of apoptosis-related proteins. Following the disruption of the lipid raft structure in IPEC-J2 cells, the apoptosis rate under OdDHL stimulation decreased by 50%. These data demonstrate that lipid rafts mediate the attachment of OdDHL to porcine intestinal cells; then, OdDHL induces apoptosis in porcine intestinal cells through the mitochondrial and death receptor pathways, thereby compromising the integrity of the porcine intestinal barrier. This study provides foundational insights into the role of QS in piglet intestinal diseases.